Psychosocial determinants of the willingness to pay for social health insurance among workers at a commercial bank in Dessie, Ethiopia: a multi-setting study - Abate, Alemayehu Mebratu; Mekonen, Asnakew Molla; Assfaw, Abebe Kibret; Toleha, Husien Nurahmed; Bayked, Ewunetie Mekashaw (Frontiers in Public Health, 2025)
BackgroundA lack of health insurance is a major barrier to the “health for all” agenda, where out-of-pocket (OOP) spending is the primary healthcare funding mechanism, a characteristic of Ethiopia’s healthcare sector, leading it to plan to fully implement social health insurance (SHI) by 2014, but not yet, owing to significant opposition from public employees. The objective of this study was to look into the psychosocial determinants of the willingness to pay (WTP) for SHI among employees at a commercial bank in Dessie, Ethiopia.MethodsWe employed a cross-sectional study (October to December 2023) design. A self-administered questionnaire was used to collect the data. We used SPSS 27 to analyze the data. The relationship between dependent and independent variables was determined using the odds ratios at a p value less than 0.05 with a 95% CI.ResultsOf 396 samples, 264 (66.7%) responded, of which 93.9% had information about SHI, mainly from broadcast media (71.0%). More than three-fourths (75.8%) and two-thirds (64.4%), respectively, had poor knowledge and a negative perception regarding SHI. More than half (50.4%) of the participants were willing to pay, of which 88.5% (40.5% of the total participants) were interested in paying the 3.0% premium set by the government. The main reason for the WTP was to help those who could not afford medical costs, while the primary reason for not paying was the scheme’s limited benefit packages. The WTP was found to be significantly affected by being female (AOR = 0.50, 95% CI: 0.26–0.98), being affiliated with orthodox Christianity (AOR = 0.48, 95% CI: 0.23–0.99), the presence of ≥5 family members in the household (AOR = 0.17, 95% CI: 0.06–0.52), experience of illness in the last 6 months (AOR = 4.95, 95% CI: 2.23–11.00), and perception toward it (AOR = 4.07, 95% CI: 2.03–8.17).ConclusionThe WTP for the scheme was suboptimal, attributed to limited benefit packages, lack of medicines and equipment, and poor healthcare quality, and significantly influenced by being female, being affiliated with orthodox Christianity, family size, experience of illness in the last 6 months, as well as perceptions toward it.